Validation of MODIS and VIIRS derived aerosol optical depth over complex coastal waters - Bilal, Muhammad; Nazeer, Majid; Nichol, Janet E. (Atmospheric research, 2017)
In this study, the Simplified Aerosol Retrieval Algorithm (SARA) was applied to both MODIS and Visible Infrared Imaging Radiometer Suits (VIIRS) images to retrieve aerosol optical depth (AOD) over water for blue, green and red wavelengths at 500m (MODISSARA) and 750m (VIIRSSARA) resolutions, respectively. Retrievals were compared with the Terra–MODIS Dark Target (DT) AOD at 3km resolution (MODIS3K) and the VIIRS Environmental Data Record (VIIRSEDR) AOD at 6km resolution. Validation was conducted using 86 Microtops II Sun photometer AOD measurements collected over different classes of water quality (low to high sediment levels) for seven days (6, 8, 9, 13, and 15, 16 and 17 October 2014) between 10:00 to 15:00 local time. Thirty-eight to fifty percent and 44–54% of the MODIS3K and the VIIRSEDR AOD retrievals respectively, fall within the expected error (EE) with root mean square error from 0.12 to 0.14 and mean absolute error from 0.10 to 0.11. The MODISSARA and the VIIRSSARA AOD retrievals are well correlated with the ground–based measurements (R: MODISSARA=0.86–0.89 and VIIRSSARA=0.85–0.94), with a larger number of retrievals falling within the EE MODISSARA=73–77% and VIIRSSARA=71–82%) than MODIS3K and VIIRSEDR. The results indicate that the SARA algorithm is more robust than MODIS3K and VIIRSEDR global AOD products, and can retrieve accurate AOD over low to highly sedimented water surfaces, similar to good AOD retrievals over land. •VIIRSEDR aerosol algorithm is sensitive to water quality, while SARA is not.•VIIRSEDR AOD over/underestimates over turbid/clear water.•MODIS3K and VIIRSEDR have similar uncertainty in AOD retrievals over water.•SARA has lower uncertainty in AOD retrievals than MODIS3K and VIIRSEDR.•SARA AOD correlates well with Microtops II AOD over different water quality levels.